Academic and Professional Values in Engineering Education: Engaging with History to Explore a Persistent Tension. Issue 1 (2nd January 2018) - Edström, Kristina
ABSTRACT: The tension between academic and professional aims of engineering education is a remarkably consistent challenge facing engineering educators. Here, some historical roots of this issue are traced through the life and work of Carl Richard Söderberg (1895–1979), who emigrated from Sweden to the US for an illustrious industrial and academic career. While Söderberg was a proponent for a more science-based curriculum, his rationale was related to solving real professional problems, and he would come to criticise the distancing of engineering education from engineering practice. Söderberg's views are compared to a present-day reform concept for engineering education, the CDIO approach, founded by MIT and three Swedish universities. The similarities show the persistence of the issue, as many of Söderberg's ideals, arguments, and proposed strategies are fully recognisable in the current discussion. Further, Söderberg and CDIO share the ideal of mutually supporting professional and disciplinary preparation, implying that the tension should not be a zero-sum game. The paths to this ideal were different, however, as Söderberg wanted to integrate theoretical aspects to improve an overly practical education, while CDIO is about improving an overly theoretical education by integrating also other necessary professional aspects.